Arsenic uptake and metabolism by a marine cyanobacteria PCC7002 - Siregar Tuti H. (E3S Web of Conferences, 2023)
Cyanobacteria Synechococcus PCC7002 is a typical marine bacterium that can tolerate salinity at around 20 ppt. In this study, cyanobacterium PCC7002 cells were incubated in a controlled environmental chamber for one week. Three different arsenic V (AsV) concentrations were added to the culture to observe the cyanobacterium’s capability to arsenic uptake. The arsenic uptake was then compared to the control media (without AsV addition). The higher the arsenic concentration added to the media, the more Arsenic occurs in the cells. Cyanobacteria cells could take up arsenic from their media at the range of 60-90% of the total arsenic exposed to the media, which showed their high arsenic tolerance. Speciation analysis using tandem HPLC and ICPMS showed that As-sugar is the main arsenic species in the cells, while inorganic arsenic is the main arsenic species in the media. Further analysis for signal confirmation using LCMS showed that the transformation of inorganic AsV into organic arsenic (As-sugar) confirmed the biotransformation of arsenic in the cyanobacteria cells. This result proves the vital role of cyanobacteria in arsenic cycling and biotransformation in marine environments.